When Business Model Innovation Creates Value for Companies: A Meta‐Analysis on Institutional Contingencies - Ilyas, Imran M.; Kammerlander, Nadine; Turturea, Roxana; van Essen, Marc (Journal of Management Studies, 2024)
AbstractUsing a meta‐analysis based on 147 primary studies from 27 countries, we synthesize extant knowledge on the relationship between business model innovation (BMI) and firm performance. Our results show that the positive BMI‐firm performance relationship is robust across various conceptualizations of and measures for BMI. Building on prior research suggesting that not all companies benefit equally from engaging in BMI, we set out to study important institutional‐level contingencies for the BMI‐performance relationship. We build on the institution‐based view as theoretical perspective and combine it with insights from the innovation literature to theorize that the magnitude of the positive effect of BMI on firm performance depends on institutional contingencies, specifically national culture and pro‐market institutions, because these national institutions affect BMI‐driven organizational learning processes. Specifically, we argue and show that the positive relationship between BMI and performance is weaker in countries characterized by high levels of masculinity and individualism, and stronger in countries characterized by high levels of customer orientation, economic freedom, and education. Besides the country‐level contingencies, the inclusion of various control variables in our meta‐analysis also reveals that, even if located in the same institutional environment, start‐up firms benefit more from BMI than mature firms and that there are no observable differences regarding BMI benefits among different industries. Moreover, a nuanced analysis shows that the positive effect on performance is stronger when BMI rely on changes in cognitive schemas compared to BMI that are of more technical nature.